Using criminological theory to explain police misconduct: a state-of-the-art review. Issue 5 (19th March 2021) - Donner, Christopher M.; Maskály, Jon; Jennings, Wesley G.; Guzman, Cynthia
Abstract : Purpose: The purpose of this paper is to review the extant published literature using traditional criminological theories in an effort to explain police misconduct. Design/methodology/approach: This paper reflects a narrative meta-review of through a search of several academic databases (e.g. Criminal Justice Abstracts, Criminology: A SAGE Full Text Collection, EBSCO Host and PsychInfo). Twenty-nine studies, across six theoretical perspectives, were identified and reviewed. Findings: The extant research generally suggests that traditional criminological theory is useful in explaining misconduct. Practical implications: The findings call on agencies to continually strengthen their recruiting and hiring processes to select recruits with suitable characteristics, and to improve their early warning systems to detect officers with patterns of problematic behavior. Also, the findings call for multiple avenues of future scholarship, namely, in theory development/integration and in refining the measurement of police misconduct. Originality/value: This paper will be useful for researchers who wish to further explore the etiology of misconduct, and for police administrators who wish to reduce the prevalence of such behavior.